Eksplorasi Kantong Semar (Nepenthes spp) di Kawasan Hulu Air Lempur Kecamatan Gunung Raya Kabupaten Kerinci - Nursanti, Nursanti; Srirahayu, Srirahayu (Jurnal Silva Tropika, 2018)
The purpose of this study was to obtain information and learn, morphological, and ecological conditions Nepenthes. This research was conducted in the Region Hulu Air Kecamatan Gunung Raya Kabupaten Kerinci. Exploration research methods implemented by the method of random roaming represented in some areas which are considered as habitat Nepenthes. Furthermore, the collection of samples and the making of herbarium, morphological data includes: the bag top, bottom bags, leaf morphology, flower morphology, and ecological data. The research result was recorded Nepenthes or pitcher plants found growing in Region Hulu Air Lempur Kecamatan Gunung Raya Kerinci that is Nepenthes ampullaria Jack, Nepenthes mirabilis (Lour) Druce, dan Nepenthes rafflesiana Jack And in the three regions, among others Pematang Ujung Tanjung, Danau Lingkat and at Kaki Bukit Gunung Batuah.